Вплив розтягування з одночасним крутінням на отримання структури зернистого перліту при сфероідізуючому відпалі - Пашинська, О. Г.; Пашинський, В. В.; Бойко, І. А.; Pashynska, O. G.; Pashynskyi, V. V.; Boiko, I. A. (Херсонська державна морська академія, 2024)
У роботі розглянуто шляхи створення ультрадрібнозернистого високоміцного дроту для забезпечення його надійності при використанні у елемантах конструкцій мостів, кранів та при виробництві шинного корду. У роботі було встановлено закономірності впливу складного навантаження крученням та розтягуванням на отримання структури зернистого перліту при сфероідізуючому відпалі. Як матеріал для досліджень використовували катанку з високовуглецевої сталі 75. У результаті крутіння та розтягування перлітні колонії деформовано, міжпластиночна відстань зростає, також збільшується частка цементитних пластин меншої довжини. Цей ефект пов'язаний з впливом дотичних напружень при крутінні та розтягуванні на тверді цементитні пластини, які крихко руйнуються під їх впливом. Встановлено, що крутіння з розтягуванням, виконане перед волочінням, приводе до подрібнення цементиту, що в свою чергу інтенсифікує процес сфероідізації та допомогає створити оптимальну структуру для проведення подальшого волочіння. Показано, що для отримання структури зернистого перліту для успішного проведення волочіння найкращою обробкою є обробка за варіантом – (гарячекатаний стан + деформація (розтяг з крутінням) + сфероідізуючий відпал).

The development of new technologies of severe plastic deformation to form strengthened ultrafinegrained state in materials is a promising way of properties increasing. Such materials demonstrate not only a high level of strength properties, but also a sufficient level of technological plasticity. In current work, ways to form an ultrafine-grained high-strength state in wire by its intensive combined deformation and heat treatment are discussed. The goal of the work was to establish the fundamentals of the influence of intensive combined plastic deformation by torsion and tension on the formation of the structure of globular pearlite during spheroidizing annealing. The wire rod made of high-carbon steel grade 75 was used for investigation. The wire from this steel is used to produce reinforced concrete parts, for manufacturing of steel ropes, and as material for metal cord. It has been shown that as a result of torsion and tension treatment, pearlite colonies are deformed, the interlamellar distance increases, and the proportion of cementite plates of shorter length also increases. This effect deals with the influence of shear stresses during treatment on brittle cementite plates, which fragment under the influence of deformation. It has been established that torsion with tension, fulfilled before drawing, activates the cementite particles refinement, which intensifies the spheroidization process and provides formation of optimal structure for further drawing. It has been shown that to obtain the structure of globular pearlite for successful drawing, the best way is wire rod processing after hot rolling according to the scheme: deformation with tension and torsion and subsequent spherodizing annealing. In this work the results of such scheme realization were considered. Positive influence of preliminary combined plastic deformation on the formation of the structure of globular pearlite during spheroidizing annealing can be used at industry for producing spheroidized wire. The effect of proposed technology on the spheroidization process can reduce the duration of the spheroidizing annealing, and this will decrease the energy consumption and oxidative decarburization of the wire surface.
The influence of tension with simultaneous rotation on obtaining the structure of globular pearlite during spheroidizing annealing
Keywords: високовуглецеві сталі; ферит; перліт; цементит; зернистий перліт; сфероідізація; дотичні напруги; мікротвердість; неоднорідність; режим обробки; high-carbon steels; ferrite; perlite; cementite; globular perlite; spheroidization; tangential stresses; microhardness; heterogeneity; processing mode